2014
DOI: 10.1097/mlr.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy-based Interventions to Reduce Primary Medication Nonadherence to Cardiovascular Medications

Abstract: BACKGROUND: Primary medication nonadherence (PMN) occurs when patients do not fill new prescriptions. Interventions to reduce PMN have not been well described. OBJECTIVES: To determine whether 2 pharmacy-based interventions could decrease PMN. DESIGN: Two sequential interventions with a control group were evaluated after completion. The automated intervention began in 2007 and consisted of phone calls to patients on the third and seventh days after a prescription was processed but remained unpurchased. The liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 17 publications
1
46
0
Order By: Relevance
“…Telephonic calls can be considered a cost‐effective and sustainable intervention to improve adherence . Live telephonic calls by a pharmacist or pharmacy technician reduced prescription abandonment (failure to pick‐up a prescription within 30 days of initial processing) by almost 5% while there was no improvement in abandonment in patients who received an automated call alone . Another study in patients with hypertension and diabetes found that a brief pharmacist telephone intervention identified barriers and improved adherence to medications among non‐adherent patients .…”
Section: Introductionmentioning
confidence: 99%
“…Telephonic calls can be considered a cost‐effective and sustainable intervention to improve adherence . Live telephonic calls by a pharmacist or pharmacy technician reduced prescription abandonment (failure to pick‐up a prescription within 30 days of initial processing) by almost 5% while there was no improvement in abandonment in patients who received an automated call alone . Another study in patients with hypertension and diabetes found that a brief pharmacist telephone intervention identified barriers and improved adherence to medications among non‐adherent patients .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as with healthcare quality more generally, quality measurement for pharmacies should encompass broad elements of quality. Despite this, studies on pharmacy quality estimate pharmacies' impact on process measures of care (Brennan et al, 2012;Fischer et al, 2014;Pringle et al, 2014) but ignore impact items like responsiveness, patient-centeredness, timeliness and efficiency. These concepts are important for a deeper understanding of the impact of pharmacies on healthcare quality, but cannot be measured easily using administrative claims databases and are not included in current pharmacy quality measurement systems (Deninger, 2015;EQuIPP, 2015a;Inland Empire Health Plan, 2014;Mascardo, 2016;Trygstad, 2015).…”
Section: A2 What Is Pharmacy Quality?mentioning
confidence: 99%
“…Estimates for rates of primary medication nonadherence (PMN) range from single digits to nearly 25% (Cheetham et al, 2013;Fischer et al, 2011;Fischer et al, 2014;Fischer et al, 2015;Jackson et al, 2014;Raebel et al, 2012;Shin et al, 2012). These estimates are for medications used to treat diseases including asthma, diabetes, hypertension, dyslipidemia and other conditions.…”
Section: B1 Primary Medication Nonadherencementioning
confidence: 99%
See 2 more Smart Citations